Kant’s philosophy in the context of modernity: on the 300th anniversary of birth - Rumyantseva, Tatsiana G. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article, dedicated to the 300th anniversary of the birth of I. Kant, shows that today his ideas have not lost their relevance and enduring signiﬁcance. The thinker’s contribution is brieﬂy outlined not only in various ﬁelds of philosophical knowledge, but also in science, culture, pedagogy, morality, international law, etc. The essence and basic provisions of his transcendent-critical philosophy were revealed. The main achievements and speciﬁcs of each of the four periods of his work were described, the main receptions and interpretations of his ideas in Western European, Russian and Belarusian philosophical thought were identiﬁed. The main vectors of the inﬂuence of his ideas in modern conditions have also been identiﬁed.
Keywords: I. Kant; 300th anniversary of birth of I. Kant; main periods of creativity of I. Kant; receptions and interpretations of teaching of I. Kant in Western European, Russian and Belarusian philosophy